1985
DOI: 10.1139/x85-049
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and the mating system of white spruce

Abstract: Inheritance of allozymes of 12 polymorphic loci was demonstrated using haploid megagametophytic tissues of viable seed from a total of 47 white spruce trees in one stand. In general, allozymes segregated as expected in a 1:1 ratio. However, one allozyme of phosphoglucose isomerase (Pgi-2) did not segregate as expected. Significant deficiency in two different heterozygous combinations was observed. This result could be indicative of selection against the allozyme. The level of genetic variability in this stand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 0 publications
5
21
2
Order By: Relevance
“…Seeds from one seed-tree (M3) even did not germinate. Loss of genetic diversity could be explained by a reduced fitness in seeds and seedlings leading to mortality, by instance through biparental inbreeding depression (Cheliak et al, 1985;Rajora et al, 2000;Hufford and Hamrick, 2003;Naito et al, 2005;Isagi et al, 2007;Duminil et al, 2009;Hasegawa et al, 2009). However, our data rather showed higher survival of offspring from related parents and fixation index showed excess of heterozygotes.…”
Section: Genetic Diversity Across Life-stagescontrasting
confidence: 59%
See 1 more Smart Citation
“…Seeds from one seed-tree (M3) even did not germinate. Loss of genetic diversity could be explained by a reduced fitness in seeds and seedlings leading to mortality, by instance through biparental inbreeding depression (Cheliak et al, 1985;Rajora et al, 2000;Hufford and Hamrick, 2003;Naito et al, 2005;Isagi et al, 2007;Duminil et al, 2009;Hasegawa et al, 2009). However, our data rather showed higher survival of offspring from related parents and fixation index showed excess of heterozygotes.…”
Section: Genetic Diversity Across Life-stagescontrasting
confidence: 59%
“…Loss of homozygote individuals seems indeed to be common in tree species (Cheliak et al, 1985;Hufford and Hamrick, 2003;Naito et al, 2005;Tamaki et al, 2009) and may result from very intensive competition for seedling establishment (Petit and Hampe, 2006) and heterozygote advantage (heterosis).…”
Section: Fixation Indexesmentioning
confidence: 99%
“…and Pinus sylvestris. A heterozygote surplus both in embryos (F = -0.066) and maternal plants (F = -0.074) was reported for Picea glauca (Moench) Voss in Ontario, Canada (Cheliak et al 1985). In a population of this species in Alberta, Canada, heterozygote deficiency was observed in adults (F = 0.039) and in embryos from two different seed crop years (F = 0.029-0.031) (King et al 1984).…”
Section: Discussionmentioning
confidence: 87%
“…The authors concluded that the even-aged, continuous stand conditions of Boreal white spruce, with accompanying high gene flow, would not favor development of genetically distinct neighborhoods. Cheliak et al (1985b) measured the mating system of a white spruce population near Whitney, Ontario from 9-year-old stored seed, and reported an average of 2% selfing, with near-random mating occurring in the stand. However, this estimate could have been biased due to mortality of heavily inbred seed as a result of selection against homozygotes during embryo development, storage and subsequent germination.…”
Section: Mating Systems Vary Among Populationsmentioning
confidence: 99%